КАЧЕСТВО ЖИЗНИ ПАЦИЕНТОВ С ПРОЛАПСОМ МИТРАЛЬНОГО КЛАПАНА - А. И. Мартынов; Е. В. Акатова; О. П. Николин (Архивъ внутренней медицины)
Patients with mitral valve prolapse (MVP) revealed a significant deterioration in the quality of life (QOL) compared with healthy people. After a course of the Magnerot, alprazolam (Xanax), psychotherapy significantly improve was estimated. In observing these same patients after 15 years recorded a decline in all QOL parameters compared to the results immediately after treatment and from baseline. However, patients with MVP who regularly used Magnerot over the years found a significant improvement of quality of life.